Manusia Madura : pembawaan, perilaku, etos kerja dan pandangan hidupnya seperti dicitrakan peribahasanya - Rifai, Mien Ahmad (Yogyakarta : Pilar Media, 2007)
Characteristics, manners, work ethic, appearance, and world view of Madurese people; study based on Madurese proverbs
Daftar Pustaka : p. 483-500
Keywords: Madurese (Indonesian people) -- Social conditions; Madurese (Indonesian people) -- Social life and customs